2005
DOI: 10.1152/ajpendo.00530.2004
|View full text |Cite
|
Sign up to set email alerts
|

Arginine synthesis does not occur during first-pass hepatic metabolism in the neonatal piglet

Abstract: We have shown that first-pass intestinal metabolism is necessary for ϳ50% of whole body arginine synthesis from its major precursor proline in neonatal piglets. Furthermore, the intestine is not the site of increased arginine synthesis observed during dietary arginine deficiency. Primed constant intravenous (iv) and intraportal (ip) infusions of L-[U-14 C]proline, and iv infusion of either L-[guanido-14 C]arginine or L-[4,5-3 H]arginine were used to measure first-pass hepatic arginine synthesis in piglets ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 32 publications
(85 reference statements)
5
29
1
Order By: Relevance
“…Arginine was extensively converted to ornithine in enterally fed piglets, particularly in those receiving a generous amount of arginine (28), and some of this ornithine may have been recycled back to arginine. A study using rat liver perfusions and isolated hepatocytes revealed that extramitochondrial arginine was converted extensively to ornithine, presumably via mitochondrial arginase II, and subsequently citrulline, in a series of reactions that appeared to be fairly tightly channeled (23).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Arginine was extensively converted to ornithine in enterally fed piglets, particularly in those receiving a generous amount of arginine (28), and some of this ornithine may have been recycled back to arginine. A study using rat liver perfusions and isolated hepatocytes revealed that extramitochondrial arginine was converted extensively to ornithine, presumably via mitochondrial arginase II, and subsequently citrulline, in a series of reactions that appeared to be fairly tightly channeled (23).…”
Section: Discussionmentioning
confidence: 99%
“…The femoral vein catheter was advanced to the vena cava to allow for the sampling of mixed venous blood. Preoperative procedures, surgical procedures, postsurgical care, and piglet housing were as previously described (28,30).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations